THE IMPLEMENTATION OF PROTOCOLS IN DENTAL PRACTICE PROCEDURES - Iulian-Costin Lupu; Raluca Elena Baciu; Dana Gabriela Budala; Roxana Vasluianu; Cătălin Silviu Tibeica; Norina Consuela Forna (Romanian Journal of Oral Rehabilitation)
The implementation of standardized protocols in dental practice are essential for ensuring a stress-free practice. Protocols are essential to a predictable and efficient modern dental management. They should cover every aspect of the practice’s work. We will thus have clinical protocols for each type of treatment and protocols for cleaning, disinfection and sterilization. For the administrative part the practice should have material acquisition protocols and communication protocols. These standardized procedures must ensure the optimisation of clinical outcomes, to enhancing patient communication, imagine and safety.